The logistics service providers in eco-efficiency innovation: an empirical study - Rossi, Silvia; Colicchia, Claudia; Cozzolino, Alessandra; Christopher, Martin (Emerald Group Publishing Limited, 2013)
Purpose: Sustainability and the search for solutions that are both efficient and ecologically sound (eco-efficient) have become topics of great interest. However, companies seeking to develop supply chain solutions that are eco-efficient are often hampered by their ability to control the wider supply chain and they may need to draw upon external support from logistics service providers (LSPs). This paper aims to explore the innovative strategies undertaken by LSPs in the eco-efficiency arena and the logistics and learning capabilities needed to achieve eco-efficiency in supply chains. Design/methodology/approach: The insights derived from a Systematic Literature Review approach to identify the most relevant articles to be included in the analysis represented the starting point for building our empirical investigation, based on case studies with in-depth interviews to investigate the phenomenon under consideration and to explore trends and evolving paradigms. Findings: The Systematic Literature Review enriches the existing literature by drawing upon three bodies of knowledge, i.e. logistics service providers, eco-efficiency and logistics innovation, and putting them into a single framework. The findings from the interviews suggest that although LSPs are well placed to implement innovative initiatives for eco-efficiency there is a range of inhibitors that prevent major change programmes. Research limitations/implications: The research reported in this paper is exploratory and limited in its scope. It is based on in-depth interviews within six companies. However, it does provide a platform from which more detailed research may be conducted. Practical implications: The managerial implications arising from the research offer a wide range of current practices in sustainability, from which strategic and operative directions to compete can be derived. Originality/value: There is little existing literature that addresses the innovative strategies undertaken by LSPs in influencing and moving supply chains towards eco-efficiency and hence the present paper is meant to help fill this gap. Keywords: Logistics Service Providers, Eco-efficiency, Logistics Innovation, Sustainable supply chain.
Keywords: Logistics Service Providers, Eco-efficiency, Logistics Innovation, Sustainable supply chain.